Ayurvedic Approach For Polycystic Ovary Syndrome And Polycystic Ovary Disease - Khatal, Satish; Gajare, Rahul; Gholap, Seema; Bhati, Kirti; Kulkarn, Mrudula; Tambe, Namrata (Journal of Neonatal Surgery, 2025)
Polycystic Ovary Syndrome and Polycystic ovary disease prevalence is 2.2%–26.0% worldwide. Child bearing women are especially susceptible. The review suggests a few plants for treatment. Herbal treatments can help with hypothyroidism, hyperplasia, obesity, diabetes, menorrhagia, sleep problems, cardiovascular disease, hyperlipidemia, hirsutism, infertility, irregular menstrual cycles, & more. Recite the Ayurvedic prayers "Swasthasya Swasthya Rakshanam" & "Aturasya Vikar Prashmanam" to keep health issues under control. Panchakarma, Rasayan, & Vajikaran are necessary for uttam santan, Ritucharya, Dincharya, & Sadvrata satvavjaya. Smoking, consuming alcohol, living in overcrowded places, eating fast food, & not getting enough sleep all contribute to bad health today. Comparison to others lowers contentment, slows digestion & metabolism, weakens the immune system, & causes a variety of health issues, including dyslipidemia, hyperacidity, khalitya, palitya, acne, pigmentation, hypertension, paralysis, stroke, cardiovascular disease, & hypothyroidism. Ayurveda states that ailments result from dosha imbalances. Ayurveda's three pillars—meditation (dhyana), yoga (pranayama), & breathing exercises (pranayama)—along with food, panchakarma (purification), & rasayana (rejuvenation) restore health.